Correlation Among Behavior, Personality, and Electroencephalography Revealed by a Simulated Driving Experiment - Yan, Lirong; Wang, Yi; Ding, Changhao; Liu, Mutian; Yan, Fuwu; Guo, Konghui (Frontiers in Psychology, 2019)
Drivers play the most important role in the human-vehicle-environment system. And the driving behaviors are significantly influenced by the cognition state of the driver and his/her personality. In this paper, we aimed to explore the correlation among driving behaviors, personality and electroencephalography (EEG) by using a simulated driving experiment. A total of 36 healthy subjects participated in the study. The 64-channel EEG data and the driving data, including the real-time position of the vehicle, the rotation angle of the steering wheel and the speed were acquired simultaneously during the driving. Cattell 16 Personality Factor Questionnaire (16PF) was utilized to evaluate the personality of the subjects. By hierarchical clustering of the 16PF personality traits, the subjects were divided into four groups, i.e. Inapprehension group, Insensitivity group, Apprehension group and Unreasoning group, who were named after their representative personality trait. Their driving performance and turning behaviors were compared. And EEG preprocessing, source reconstruction and comparison among four groups were performed using Statistical Parameter Mapping (SPM). The turning process of the subjects can be formulated into two steps, rotating the steering wheel toward the turning direction and entering the turn, and then rotating the steering wheel back and leaving the turn. The bilateral frontal gyrus was found to be activated when turning left and right which might be associated with its function in attention, decision-making and executive control functions in visual-spatial and visual-motor processes. Unreasoning group had the worst driving performance with highest times of car collision and the most intensive driving action, which was related with the higher load of visual spatial attention and decision making, when occipital and superior frontal areas played the very important role. Apprehension (O) and Tension (Q4) had positive correlation, and Reasoning (B) had negative correlation with dangerous driving behaviors. Our results demonstrated the close correlation among driving behaviors, personality and EEG and may be taken as reference for the prediction and precaution of the dangerous driving of people with specific personality traits.